1997
DOI: 10.1002/(sici)1097-0010(199709)75:1<19::aid-jsfa830>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seed roasting temperature and time on the quality characteristics of sesame (Sesamum indicum) oil

Abstract: The quality characteristics and composition of sesame oils prepared at di †erent roasting temperatures (160È250¡C) from sesame seeds using a domestic electric oven were evaluated as compared to an unroasted oil sample : only minor increases (P \ 0É05) in characteristics, such as peroxide value, carbonyl value, anisidine value and thiobarbituric acid reactive substances, of sesame oils occurred in relation to increasing roasting temperature and time between 160 and 200¡C, but colour units of oils increased mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 3 publications
4
22
0
Order By: Relevance
“…Overall, the roasting did not have a significant influence on the fatty acid compositions of the extracted oil with few exceptions for the oil extracted after oven drying process. Roasting in oven marginally increased the percentage of palmitic (C16:0) and oleic acids (C18:1), and decreased the linoleic acid (C18:2) which is supported by the observation made by Yoshida & Takagi (1997) for roasted sesame seed oil. A decrease in SFA and PUFA was observed in the roasted oil samples, and the observation in accordance with the observation of Yoshida et al (1999); they observed a decrease in the PUFA content in soybean oil during microwave roasting.…”
Section: Fatty Acid Compositionsupporting
confidence: 64%
“…Overall, the roasting did not have a significant influence on the fatty acid compositions of the extracted oil with few exceptions for the oil extracted after oven drying process. Roasting in oven marginally increased the percentage of palmitic (C16:0) and oleic acids (C18:1), and decreased the linoleic acid (C18:2) which is supported by the observation made by Yoshida & Takagi (1997) for roasted sesame seed oil. A decrease in SFA and PUFA was observed in the roasted oil samples, and the observation in accordance with the observation of Yoshida et al (1999); they observed a decrease in the PUFA content in soybean oil during microwave roasting.…”
Section: Fatty Acid Compositionsupporting
confidence: 64%
“…www.advancedsciencenews.com www.ejlst.com refining process, resulting in the higher oxidation stability of sesame oil. [35][36][37][38] Typically, the degradation of C18:1 is slower than that of C18:2, [39] so the decomposition rate of UFA in the olive, safflower, and rapeseed oils, in which C18:1 was the dominant fatty acid, was relatively slow. The content of C18:2 was much greater in the soybean and corn oils, so the rate of decomposition of UFA in these oils was great.…”
Section: Changes In the Fatty Acid Compositions Of The Oil Samples Dumentioning
confidence: 99%
“…Sesame seed oil has high content of linoleic acid and oleic acid followed by palmitic acid and stearic acid (Gharby et al, 2015;Yoshida & Takagi 1997). Addition of sesame powder to puffed corn snack materials caused significant changes (p < .05) in the fatty acid profile (Table 1).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Earlier researches showed that sesamols were more effective at increasing the stability of oils than tocopherol and they can also have a positive synergetic action with γ-tocopherol (Yoshida & Takagi, 1997.…”
Section: Sesamin and Sesamolinmentioning
confidence: 99%